2020
DOI: 10.1177/1557988320945458
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Runt-Related Transcription Factor 2 Are Associated With Poor Survival of Patients With Idiopathic Pulmonary Arterial Hypertension

Abstract: Runt-related transcription factor 2 (RUNX2) plays a pivotal role in the pathogenesis of pulmonary arterial hypertension (PAH); yet, whether circulating levels of RUNX2 can predict survival of patients with idiopathic PAH (IPAH) is still unclear. The present study aimed to investigate the correlation between circulating levels of RUNX2 and survival of patients with IPAH. Blood samples were collected from 46 incident patients with IPAH and 30 healthy controls in Shanghai Pulmonary Hospital. Levels of RUNX2 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…HSPA5 [376], RIN3 [350], PTN (pleiotrophin) [339], DISC1 [398], hsa-mir-378a-5p [551], hsa-mir-5010-3p [552] and hsa-mir-21-3p [553] are believed to be associated with neurological and psychological problems. F2RL1 [58], B2M [236], TCF4 [237], hsa-mir-34b-5p [554], hsa-mir-21-3p [455], SOX2 [456], GATA2 [557], RUNX2 [558], TEAD4 [559], DROSHA [560], STAT5A [561] and ESR1 [562] are believed to be associated with hypertension. A previous study found that increased PLK1 [130], B2M [170], SOCS1 [128], AR (androgen receptor) [166], hsa-mir-21-3p [563], GATA2 [564], RUNX2 [565] and ESR1 [566] expression were associated with cardiovascular problems.…”
Section: Discussionmentioning
confidence: 99%
“…HSPA5 [376], RIN3 [350], PTN (pleiotrophin) [339], DISC1 [398], hsa-mir-378a-5p [551], hsa-mir-5010-3p [552] and hsa-mir-21-3p [553] are believed to be associated with neurological and psychological problems. F2RL1 [58], B2M [236], TCF4 [237], hsa-mir-34b-5p [554], hsa-mir-21-3p [455], SOX2 [456], GATA2 [557], RUNX2 [558], TEAD4 [559], DROSHA [560], STAT5A [561] and ESR1 [562] are believed to be associated with hypertension. A previous study found that increased PLK1 [130], B2M [170], SOCS1 [128], AR (androgen receptor) [166], hsa-mir-21-3p [563], GATA2 [564], RUNX2 [565] and ESR1 [566] expression were associated with cardiovascular problems.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the RUNX gene family is associated with levels of immune infiltration, poor prognosis, and drug response in various types of cancer. In addition, these findings highlight the potential use of members of the RUNX gene family as biomarkers for cancer progression and prognosis, and as potential treatment targets in various cancer types [ 36 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the RUNX gene family is associated with levels of immune in ltration, poor prognosis, and drug response in various types of cancer. In addition, these ndings highlight the potential use of members of the RUNX gene family as biomarkers for cancer progression and prognosis, and as potential treatment targets in various cancer types [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%